2007
DOI: 10.1152/ajpcell.00221.2006
|View full text |Cite
|
Sign up to set email alerts
|

Isoflurane preconditioning uncouples mitochondria and protects against hypoxia-reoxygenation

Abstract: Ischemic cardiac injury can be substantially alleviated by exposing the heart to pharmacological agents such as volatile anesthetics before occurrence of ischemia-reperfusion. A hallmark of this preconditioning phenomenon is its memory, when cardioprotective effects persist even after removal of preconditioning stimulus. Since numerous studies pinpoint mitochondria as crucial players in protective pathways of preconditioning, the aim of this study was to investigate the effects of preconditioning agent isoflur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
94
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 74 publications
(102 citation statements)
references
References 57 publications
(51 reference statements)
7
94
1
Order By: Relevance
“…These data suggest that oyster mitochondria undergo minimal functional alterations during the prolonged "shutdown" in anoxic tissues, and the only significant functionally relevant change is a reduction in mitochondrial RCR. A similar moderate decrease in RCR without a concomitant decline in oxidation capacity was found in mammalian mitochondria during hypoxia/reoxygenation-resistant states induced by ischemic preconditioning or by pharmacological agents and was interpreted as a sign of mild uncoupling that serves as a protection mechanism against elevated ROS formation and associated mitochondrial and tissue damage (44,48,52). Possibly a similar mechanism is involved in mitochondrial protection during postanoxic recovery in oysters.…”
Section: Discussionsupporting
confidence: 58%
“…These data suggest that oyster mitochondria undergo minimal functional alterations during the prolonged "shutdown" in anoxic tissues, and the only significant functionally relevant change is a reduction in mitochondrial RCR. A similar moderate decrease in RCR without a concomitant decline in oxidation capacity was found in mammalian mitochondria during hypoxia/reoxygenation-resistant states induced by ischemic preconditioning or by pharmacological agents and was interpreted as a sign of mild uncoupling that serves as a protection mechanism against elevated ROS formation and associated mitochondrial and tissue damage (44,48,52). Possibly a similar mechanism is involved in mitochondrial protection during postanoxic recovery in oysters.…”
Section: Discussionsupporting
confidence: 58%
“…However, it is unclear what mediates mitochondrial depolarization by APC. It is suggested that mitochondrial K ϩ channels, often identified as effectors of protection by preconditioning, could be these mediators (10,27,32,34). However, their role in this mechanism is questionable since their activation has been correlated with both increase and decrease in ROS production (20,49).…”
Section: Discussionmentioning
confidence: 99%
“…The ⌬⌿m-sensitive fluorescent dye tetramethylrhodamine ethyl ester (TMRE) (Invitrogen, Carlsbad, CA) and autofluorescence of mitochondrial flavoproteins (FPs) were used for the assessment of ⌬⌿ m in cardiomyocytes (Fig. 1A) as previously described (32). Excitation and emission Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…ATP synthesis rates by isolated mitochondria was assessed using a chemiluminescence-based method utilizing firefly luciferase and luciferin (ATP Determination Kit; Invitrogen), as described previously (Ljubkovic et al, 2007). The reaction solution contained respiration buffer, 0.2 M diadenosine pentaphosphate, 5 mM pyruvate, 5 mM malate, 2 mg/l mitochondria, 200 M luciferin, and 1.25 mg/l luciferase.…”
Section: Mitochondrial Isolation and Functional Assaysmentioning
confidence: 99%